A Comparison between the Antimicrobial Effects of Triple Antibiotic Paste and Calcium Hydroxide against Entrococcus Faecalis - Alireza Adl; Nooshin Sadat Shojaee; Mohamad Motamedifar (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2012)
Introduction: The purpose of this study was to determine the in vitro antimicrobial ability against Entrococcus (E.) faecalis of triple antibiotic paste and its components compared with calcium hydroxide mixtures.Materials and Methods: An agar well diffusion assay and MIC method were used to determine the efficacy of the experimental medicaments in removing E. faecalis. Medicaments were divided into 9 groups; triple antibiotic powder with saline or chlorhexidine, metronidazole, ciprofloxacin, minocycline antibiotics were also separately tested (with normal saline), and Ca(OH)2 plus normal saline or with 2% chlorhexidine. These medicaments were evaluated at four concentrations of 25, 50, 100 and 200 µg per mL in an agar well diffusion test. The diameters of the growth inhibition zones for each group were recorded and compared. The minimum inhibitory concentrations (MIC) of tested medicaments that are required to kill E. faecalis were also determined. The differences between groups were analyzed by Kruskal-Wallis and Mann-Whitney U tests. Results: The largest inhibition zones were observed for the triple antibiotic mixture/saline, triple antibiotic mixture/2% chlorhexidine and minocycline/saline, and the smallest for Ca(OH)2/saline, Ca(OH)2/2% chlorhexidine. Concentration increases produced greater antibacterial effects in all groups. The MIC determination method showed similar results. Conclusion: The results suggest that the triple antibiotic paste with either 2% chlorhexidine or normal saline would be the preferred medicament against E. faecalis and, among its three components, minocycline has the greatest antibacterial effect.